Semantic Transfer and Lexical Errors in English Writing among Undergraduates’ Saudi Male Students - Falah Altamimi, Dheifallah Hussein (Forum for Linguistic Studies, 2025)
Arab students who learn English as a foreign language, especially Saudi students, face several challenges during the process of mastering writing skills. This research addresses the problem of persistent lexical errors in students’ academic writing, which stem from semantic transfer between Arabic and English. The main purpose of this study is to identify and categorize the most common lexical errors caused by semantic transfer from Arabic to English in the academic writing of Saudi undergraduates’ students and to examine the perceived causes of lexical errors caused by semantic transfer from Arabic to English. The main research question is: What are the most common lexical errors caused by semantic transfer from Arabic to English in the academic writing among Saudi male undergraduates’ students? The research participants were 20 male students from the Languages and Translation Department at the University College of Haql, University of Tabuk. Using a mixed-methods approach to examine lexical errors caused by semantic transfer from Arabic to English. Quantitative data from 100 student essays were analyzed descriptively to identify common errors, while qualitative insights were gathered through a semi-structured group interview and analyzed thematically to explore students’ perceptions of the causes. The findings reveal that the most common lexical errors through the semantic transfer are direct translations, word choice errors, false cognates, and incorrect collocations. The semi-structured interview revealed four main causes of these errors: negative transfer from Arabic, overgeneralization of English rules, limited exposure to authentic English, and insufficient awareness of collocations.